FRI0449 Analysis of the canadian adalimumab post-marketing observational epidemiological study assessing effectiveness in ankylosing spondylitis (complete-as): association between baseline extra articular manifestations and patient-reported outcomes. (15th June 2017) - Bessette, L; Haraoui, B; Khraishi, M; Bensen, W; Remple, VP
Abstract : Background: Ankylosing spondylitis (AS) is an immune mediated inflammatory disease. Although characterized by axial and peripheral joint manifestations, extra articular manifestations (EAMs) are a common clinical feature. EAMs have been found to negatively impact health outcomes including quality of life and work capacity. Objectives: The aim of this analysis was to describe the prevalence of EAMs at baseline and assess their association with patient-reported outcomes (PROs) in a Canadian routine clinical care setting. Methods: COMPLETE-AS is an ongoing observational study expected to enroll 1120 AS patients from 60–80 sites across Canada. All patients enrolled between June/2011 - October/2015 were included in this analysis. Eligible patients are anti-TNFα naïve adults, with active AS as per the judgment of the treating physician, who require change in current AS treatment. Baseline disease parameters assessed were EAMs (collected from medical chart, physician assessment or patient report), disease activity (BASDAI) and functional status (BASFI); baseline PROs assessed were related to mental health (BDI-II), work limitations (WLQ), and quality of life (QoL; SF-36 Physical (PCS) and Mental (MCS) component summaries). Multivariate linear regression models adjusting for baseline BASDAI and BASFI assessed the impact of EAMs on PROs. Results: A total of 569 patients were included in the current analysis. Mean (SD) age and duration of disease was 43.3 (13.4) and 5.9 (9.8) years, respectively. The majority of patients enrolled were male (57.1%), Caucasian (86.1%), HLA B27 + (67.0%), and RF - (93.7%). The most common baseline EAM reported was enthesitis (15.3%), followed by psoriasis (13.0%), inflammatory bowel disease (IBD; 9.1%), and uveitis (3.2%). EAM combination 1 (EAM1: all EAMs) and EAM combination 2 (EAM2: excluding psoriasis), was reported by 33.2%, and 23.7% of patients, respectfully. Regression analysis adjusting for baseline BASDAI and BASFI, found enthesitis, EAM1, and EAM2 to be significant negative predictors of SF-36 PCS scores (p<0.05). Individual EMAs were not found to impact PROs, except for uveitis, found to be a negative predictor of SF-36 PCS scores for which a statistical trend was identified (p<0.15). No association between EAMs and SF-36 MCS, BD-II or WLQ scores were found. Conclusions: In a Canadian routine clinical care setting, a substantial proportion of AS patients requiring a change in treatment report EAMs. Patients with EAMs were found to have significant reduction in baseline QoL specifically related to physical functioning. Acknowledgements: The authors wish to acknowledge JSS Medical Research, Montreal (QC) Canada for statistical analysis, medical writing and editorial assistance during the preparation of this abstract. Disclosure of Interest: L. Bessette Consultant for: Janssen, Roche, UCB, AbbVie, Pfizer, Celgene, Lilly, Novartis, Speakers bureau: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Lilly, Novartis, B. Haraoui Grant/research support from: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, and UCB; Speaking engagements: Amgen, BMS, Janssen, Pfizer, and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Eli Lilly, Janssen, Merck, Pfizer, Roche, and UCB, Speakers bureau: Amgen, BMS, Janssen, Pfizer, and UCB, M. Khraishi Consultant for: AbbVie, Speakers bureau: AbbVie, W. Bensen Consultant for: Abbvie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Merck, Pfizer, Roche, and UCB, Speakers bureau: Abbvie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Merck, Pfizer, Roche, and UCB, V. Remple Shareholder of: AbbVie Corp., Employee of: AbbVie Corp.